Defect Passivation on Lead-Free CsSnI3 Perovskite Nanowires Enables High-Performance Photodetectors with Ultra-High Stability - Gao, Zheng; Zhou, Hai; Dong, Kailian; Wang, Chen; Wei, Jiayun; Li, Zhe; Li, Jiashuai; Liu, Yongjie; Zhao, Jiang; Fang, Guojia (Nano-Micro Letters, 2022)
In recent years, Pb-free CsSnI3 perovskite materials with excellent photoelectric properties as well as low toxicity are attracting much attention in photoelectric devices. However, deep level defects in CsSnI3, such as high density of tin vacancies, structural deformation of SnI6− octahedra and oxidation of Sn2+ states, are the major challenge to achieve high-performance CsSnI3-based photoelectric devices with good stability. In this work, defect passivation method is adopted to solve the above issues, and the ultra-stable and high-performance CsSnI3 nanowires (NWs) photodetectors (PDs) are fabricated via incorporating 1-butyl-2,3-dimethylimidazolium chloride salt (BMIMCl) into perovskites. Through materials analysis and theoretical calculations, BMIM+ ions can effectively passivate the Sn-related defects and reduce the dark current of CsSnI3 NW PDs. To further reduce the dark current of the devices, the polymethyl methacrylate is introduced, and finally, the dual passivated CsSnI3 NWPDs show ultra-high performance with an ultra-low dark current of 2 × 10–11 A, a responsivity of up to 0.237 A W−1, a high detectivity of 1.18 × 1012 Jones and a linear dynamic range of 180 dB. Furthermore, the unpackaged devices exhibit ultra-high stability in device performance after 60 days of storage in air (25 °C, 50% humidity), with the device performance remaining above 90%. Highlights: 1 Through materials analysis and theoretical calculations, the defects of CsSnI3 nanowires (NWs) were effectively passivated via incorporating 1-butyl-2,3-dimethylimidazolium chloride into perovskites. 2 The high-performance CsSnI3 NW photodetectors (PDs) were achieved with a responsivity of up to 0.237 A W−1, a high detectivity of 1.18 × 1012 Jones and a linear dynamic range of 180 dB. These values are comparable to the reported high-performance Pb-based perovskite PDs and higher than those of the Pb-free perovskite PDs. 3 Our unpackaged devices exhibit ultra-high stability with no degradation after 60 days of storage in air (25 °C, 50% humidity).